Spatial Assessment of Aquifer Vulnerability Using Dar Zarrouck Parameters in Idunmwowina, Edo State, Nigeria - Ojeaga, K.; Ehinlaiye, A. O. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2025)
Rapid urbanization and unregulated sand mining in many semi-urban areas of Edo State have heightened concerns about aquifer vulnerability and groundwater contamination. This study evaluated the spatial variability of aquifer vulnerability in Idunmwowina, Ovia North-East Local Government Area, Edo State, using Dar Zarrouk parameters derived from vertical electrical sounding (VES). Five VES were conducted with the Schlumberger configuration at a maximum current electrode spacing of AB/2 = 200 m. Data interpretation was carried out using the partial curve matching technique in Surfer software, while kriging interpolation was applied for spatial mapping. The geoelectric curves identified include KHK (40%), HAA (20%), HAK (20%), and AAK (20 %), indicating predominantly semi-confined aquifers. The results of Dar Zarrouk parameters revealed hydraulic conductivity values ranging from 0.73–1.46 m/day, transmissivity between 2.72–7.67 m²/day, transverse resistance from 26,621–221,682 Ωm², and longitudinal conductance (S) values between 0.004–0.335 Ω⁻¹ (mean = 0.0752 Ω⁻¹). Additionally, the Spatial distribution maps showed higher transmissivity and hydraulic conductivity in the southwestern part of the study area, while longitudinal conductance values were generally low, suggesting weak aquifer protective capacity. Therefore, the results indicate that the aquifer system is vulnerable to contamination from leachates generated by nearby dumpsites. It It highlights the need for effective land use management and sustainable waste disposal practices to safeguard groundwater resources in the area.